1999
DOI: 10.1172/jci4891
|View full text |Cite
|
Sign up to set email alerts
|

Biologic significance of angiopoietin-2 expression in human hepatocellular carcinoma

Abstract: MethodsPatients. We studied 23 patients with resectable HCC. Tumor size varied from 1.8 cm to 14.5 cm, and all individuals had a single tumor. At the time of surgery, wide resection margins allowed us to obtain enough tissues to compare gene expres-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
164
2
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(178 citation statements)
references
References 16 publications
8
164
2
4
Order By: Relevance
“…The adherent cells were examined at 4006 magni®cation, and the stained cells were counted in four di erent random locations, each containing approximately 250 cells. The percentage of apoptotic cells is based on the sum of the¯oating cells plus the apoptotic adherent cells in a given cell population Angiopoietin-2 survival pathway in endothelial cells I Kim et al mRNA are observed in highly vascularized glioblastoma and hepatocellular carcinoma (Stratmann et al, 1998;Tanaka et al, 1999). Moreover, our recent study indicates that expression of Ang2 mRNA is detected not only in primary endothelial cells, but also in several non-endothelial tumor cell lines, primary tumor tissues, and macrophages (Kim et al, 2000b).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The adherent cells were examined at 4006 magni®cation, and the stained cells were counted in four di erent random locations, each containing approximately 250 cells. The percentage of apoptotic cells is based on the sum of the¯oating cells plus the apoptotic adherent cells in a given cell population Angiopoietin-2 survival pathway in endothelial cells I Kim et al mRNA are observed in highly vascularized glioblastoma and hepatocellular carcinoma (Stratmann et al, 1998;Tanaka et al, 1999). Moreover, our recent study indicates that expression of Ang2 mRNA is detected not only in primary endothelial cells, but also in several non-endothelial tumor cell lines, primary tumor tissues, and macrophages (Kim et al, 2000b).…”
mentioning
confidence: 87%
“…However, when co-administered with VEGF, both Ang1 and Ang2 augmented the formation of neovessels (Asahara et al, 1998). Ectopic expression of Ang2 in Ang2 nonexpressing cells promotes tumor angiogenesis when those cells are implanted in nude mice (Tanaka et al, 1999). In vitro experiments have shown that Ang1 has speci®c e ects on endothelial cells: it potently induces chemotactic response (Witzenbichler et al, 1998), network formation , sprouting (Koblizek et al, 1998;Kim et al, 1999) and survival in apoptosis Kim et al, 2000a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, high levels of Ang2 by tumor or vascular tissues have been documented in a wide variety of highly vascularized tumors such as malignant glioblastoma [54][55][56], nonsmall cell lung cancer [57,58], hepatocellular carcinoma [59][60][61][62], gastric carcinoma [63], Kaposi's sarcoma and angiosarcoma [64], neuroblastoma [65] and thyroid tumor [66] (see Tab 1). Further, Ang2 expression has been correlated with poor prognosis in NSCLC [67], HCC [62], gastric [63] and breast [68] cancers.…”
Section: Angiopoietin Expression In Tumorsmentioning
confidence: 99%
“…Further, Ang2 expression has been correlated with poor prognosis in NSCLC [67], HCC [62], gastric [63] and breast [68] cancers. In addition, HT29 colon cancer, hepatocellular carcinoma, and MKN-7 gastric cancer cells engineered to overexpress Ang2 demonstrated augmented tumor growth and vessel count compared to vector controls [59,63,69]. In many cases, VEGF overexpression is observed as well, suggesting that destabilization by Ang2 permits VEGF-induced angiogenesis to proceed (see Tab 1).…”
Section: Angiopoietin Expression In Tumorsmentioning
confidence: 99%